2010
DOI: 10.1002/bies.201000043
|View full text |Cite
|
Sign up to set email alerts
|

Function and evolution of sex determination mechanisms, genes and pathways in insects

Abstract: Animals have evolved a bewildering diversity of mechanisms to determine the two sexes. Studies of sex determination genes – their history and function – in non-model insects and Drosophila have allowed us to begin to understand the generation of sex determination diversity. One common theme from these studies is that evolved mechanisms produce activities in either males or females to control a shared gene switch that regulates sexual development. Only a few small-scale changes in existing and duplicated genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
173
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(179 citation statements)
references
References 100 publications
(175 reference statements)
5
173
0
1
Order By: Relevance
“…What is then the molecular mechanism that controls the sexual development in S. cynthia ssp.? It is now generally accepted that the doublesex (dsx) acts as a double switch gene at the bottom of sex-determining pathway in insects (Suzuki, 2010;Gempe and Beye, 2011), and we can assume that the dsx gene plays this role also in S. cynthia ssp. However, upstream components of the sex-determining pathway in S. cynthia ssp.…”
Section: Discussionmentioning
confidence: 99%
“…What is then the molecular mechanism that controls the sexual development in S. cynthia ssp.? It is now generally accepted that the doublesex (dsx) acts as a double switch gene at the bottom of sex-determining pathway in insects (Suzuki, 2010;Gempe and Beye, 2011), and we can assume that the dsx gene plays this role also in S. cynthia ssp. However, upstream components of the sex-determining pathway in S. cynthia ssp.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have indicated that most of the known sex determination genes discovered so far in vertebrates are derived from the duplicated homologs of Dmrt1 gene (Chong et al, 2013;Gamble and Zarkower, 2012;Gempe and Beye, 2011;Graves, 2013;Herpin and Schartl, 2011;Kikuchi and Hamaguchi, 2013;Matson and Zarkower, 2012;Siegal and Baker, 2005;Zhou and Gui, 2010). For gibel carp, as a unisexual lineage that is able to utilize gynogenesis as a unisexual reproduction mode, how male individuals arise and how male determination genes evolve will be the merit for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although upstream sex-determination signals are diverse and changeable among species, the genes involved in the pathway are relatively conserved, which commonly contain the DNA binding motif (DM) domain (Gempe and Beye, 2011;Matson and Zarkower, 2012;Siegal and Baker, 2005;Zarkower, 2013). Especially, the Dmrt1 (dsx and mab-3 related transcription factor 1) gene had been revealed to play important roles in sex differentiation and testis development of vertebrates (Herpin and Schartl, 2011;Matson and Zarkower, 2012;Xia et al, 2007;Zarkower, 2013), and many sexdetermination or sex chromosome-linked genes had been demonstrated to be the duplicated homologs of Dmrt1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Both proteins share the N-terminal domain, which contains a DNA-binding domain (DM domain). However, they differ in their C-terminal domains, which endow specific functions to these proteins (Burtis and Baker 1989;Hoshijima et al 1991).The search for genes orthologous to the sex-determination genes of D. melanogaster has been undertaken in other insects (reviewed in Sánchez 2008;Gempe and Beye 2010;Verhulst et al 2010). This was a first task of our Sciara project.…”
mentioning
confidence: 99%